2020
DOI: 10.1111/spol.12574
|View full text |Cite
|
Sign up to set email alerts
|

Frontline managers' perceptions and justifications of behavioural conditionality

Abstract: The debate on behavioural conditionality is characterised by abundant controversies. Frontline managers have a particularly important role in implementing these policies because their interpretation of the welfare policies regulates the frameworks of street‐level bureaucrat's discretionary powers. A nationwide survey among frontline managers in the Norwegian Labour and Welfare Administration revealed that 86% of the managers expressed strong normative support towards welfare conditionality. With this as a back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
2
16
0
4
Order By: Relevance
“…The same perspective is identified at a range of political parties that support mandatory activation based on human capital and paternalistic concerns (Eriksen & Molander, 2018). Both NAV managers (Sadeghi & Terum, 2020) and caseworkers (Gjersøe, Leseth, & Vilhena, 2019;Terum, Torsvik, & Øverbye, 2017) express the same positive and 'caring' approach. These findings differ from international studies (Watts & Fitzpatrick, 2018, p. 99), suggesting thus the need for a broader understanding of sanctions in welfare policy.…”
Section: Social Assistance In Norwaymentioning
confidence: 86%
“…The same perspective is identified at a range of political parties that support mandatory activation based on human capital and paternalistic concerns (Eriksen & Molander, 2018). Both NAV managers (Sadeghi & Terum, 2020) and caseworkers (Gjersøe, Leseth, & Vilhena, 2019;Terum, Torsvik, & Øverbye, 2017) express the same positive and 'caring' approach. These findings differ from international studies (Watts & Fitzpatrick, 2018, p. 99), suggesting thus the need for a broader understanding of sanctions in welfare policy.…”
Section: Social Assistance In Norwaymentioning
confidence: 86%
“…The act's several mitigation clauses leave rather substantial room for caseworkers' discretionary power. Previous studies from Norway indicated that managers and caseworkers use their discretionary power in the implementation of conditionality and sanctions (Gjersøe et al, 2020;Sadeghi & Terum, 2020).…”
Section: Legal and Institutional Contextmentioning
confidence: 99%
“…Aquí las sanciones son mucho más reducidas y se aplican de forma discrecional por los profesionales, con una concepción pedagógica, de forma suave, evitando la desprotección, y orientadas por el mejor interés del usuario. Las actividades y el empleo se entienden positivas para el mantenimiento o la potenciación del capital humano (Sadeghi y Terum, 2020) En lo que sigue mostraremos, a partir del caso navarro, cómo las políticas de integración de servicios sociales y de empleo gradualistas en el ámbito subestatal pueden ir también asociadas a concepciones de la activación más cercanas a este modelo socialdemócrata, incluso en un contexto estatal propio del modelo mediterráneo, como es el caso de España.…”
Section: Las Lecciones Del Análisis De Las Experiencias Europeasunclassified